A light-responsive molecular switch based on cucurbit[7]uril and 1, 1′-bis(benzyl)-4-[2-(4-pyridyl)-vinyl]-pyridinium dibromide displaying white light emission. Issue 6 (21st January 2022) - Wang, Qin; Zhang, Kun; Lin, Rui-Lian; Sun, Wen-Qi; Ye, Ming-Fu; Xiao, Xin; Liu, Jing-Xin
Abstract : In this work, we designed and synthesized a light-responsive molecular switch, in which the switching states can emit cold white fluorescence under UV light. Abstract : By using 1 H NMR, ESI-MS and UV spectra, a novel light-responsive molecular switch constructed using 1, 1′-bis(benzyl)-4-[2-(4-pyridyl)-vinyl]-pyridinium (1 2+ ) and cucurbit[7]uril (Q[7]) is demonstrated. The E - to Z -isomerization of the double bond in 1 2+ results in the transition of the switching states from the 1 : 2 complex E -1 2+ @Q[7]2 to the stable 1 : 1 complex Z -1 2+ @Q[7]. In particular, both the 1 : 2 complex and the 1 : 1 complex can emit cold white fluorescence under UV light.